Silicon microsystems for neuroscience and neural prostheses. - Wise, K.D.
Silicon-based microsystems are being developed to interface with the central nervous system (CNS) at the cellular level. Dense three-dimensional (3-D) microelectrode arrays with as many as several hundred sites permit acute and semichronic single-unit recording and stimulation, while on-chip circuitry for site selection, amplification, and multiplexing reduces noise and limits the number of output leads to manageable levels. Hybrid implant-mounted circuitry can be used to separate single units from baseline noise and provide simultaneous wireless access to more than a hundred information channels. This article focuses on the technology for electronically interfacing with the CNS at the cellular level. Devices based on silicon-on-insulator technology and silicon array structures not based as directly on the planar processes of ICs are given notice. Tissue interface and cabling problems still exist for long-term applications but the basic technology platform is robust and should allow engineering solutions to be developed over time. Present technology is consistent with real breakthroughs in our understanding of the brain at the circuit/system level during the coming decade though detailed mapping that has been impossible in the past. Such mapping could also serve as a basis for prosthetic devices for treating some of mankind's most debilitating disorders.
Keywords: Si; Amplification; Brain; Cabling problems; Cellular level; Central nervous system; Debilitating disorders; Dense three-dimensional microelectrode arrays; Hybrid implant-mounted circuitry; Multiplexing; Neural prostheses; Neuroscience; On-chip circuitry; Prosthetic devices; Silicon array structures; Silicon microsystems; Silicon-on-insulator technology; Site selection; Tissue interface